Meningkatkan Kemampuan Numerasi Anak Usia 5-6 Tahun melalui Pembelajaran STEAM dan Bahan Loose Parts - Denisa Ayu Raniah; Nur Ika Sari Rakhmawati (Departement of Mathematics Education, 2023)
This study aims to examine the effect of STEAM learning using loose parts materials on numeracy skills in children aged 5-6 years. During the observation, several kindergartens in Surabaya were found to have low numeracy skills among the children. The low numeracy skills in children aged 5-6 years are caused by the general nature of mathematics education, which is rarely linked to activities or daily life. However, numeracy skills can help children solve everyday life problems. This study adopts a quantitative approach with a Quasi Experimental Design. The research subjects consisted of 54 children divided into an experimental group and a control group. Data were collected through observation techniques. To ensure data reliability, consistency testing was conducted using the interrater reliability method with Cronbach's alpha analysis. Data analysis was performed using the Independent Sample T-test technique. The results of this study indicate that STEAM learning using loose parts materials has a significant effect on numeracy skills in 5-6-year-old children in Group B.